Towards a phonological typology of Uralic languages - Pajusalu, Karl; Uiboaed, Kristel; Pomozi, Péter; Németh, Endre; Fehér, Tibor (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2018)
The paper focuses on phonological similarities between Uralic languages. The study is based on a dataset which includes 33 word-prosodic and segmental features of 28 Uralic languages or main dialects, including all traditional subgroups of the language family. In statistical analysis clustering and dimension reduction techniques such as multidimensional scaling are applied. This methodology enables to explore distinctive subgroups of languages as well as calculate distances between languages and language groups. As a result we present a quantitative phonological typology. The main division appears between western and central-eastern phonological types of the Uralic languages. The detected phonological subgroups coincide with the traditional ones, i.e. Finnic, Saami, Mordvin, Mari, Permic, Hungarian, Ob-Ugric and Samoyedic. The Hungarian subgroup (Standard Hungarian, Csángó Hungarian) and the Ob-Ugric subgroup (Northern Mansi, Eastern Mansi, Northern Khanty, Eastern Khanty) are internally stable. However, their interrelation and relationship with other groups is ambiguous; according to our results, Hungarian is typologically closer to the Western Uralic language groups (i.e. Finnic and Saami), whereas Ob-Ugric languages form a distinct branch of Central-Eastern Uralic. In general, the results reveal a significant influence of multiple areal connections on the phonological formation of Uralic languages.Аннотация. Карл Паюсалу, Кристел Уйбоаэд, Петер Помози, Эндре Немет и Тибор Фехер: К фонологической типологии уральских языков. В статье рассматриваются фонологические сходства между уральскими языками. Исследование основывается на выборке данных, которая включает 33 просодических и сегментных признака, которые применяются к 28 уральским языкам или их основным диалектам. Эта выборка покрывает все традиционно выделяемые группы уральской семьи. Для статистической обработки данных используются методы кластерного анализа и многомерного шкалирования. Такой подход позволяет исследовать выявленные подгруппы языков и ...